1982
DOI: 10.1038/jcbfm.1982.52
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Na+, K+-ATPase Activity during Exposure to and Recovery from Acute Ischemia

Abstract: This study documents the Na+,K+-ATPase activity as well as selected parameters of oxidative metabolism and electrophysiological function in rat brain exposed to ischemia produced by electrocautery of the vertebral arteries and reversible occlusion of the carotid arteries. During a 0.5-h ischemic exposure in which the electroencephalograph (EEG) was abolished and energy metabolism severly compromised the Na+,K+-ATPase showed a capability for enhanced activity (120-140% of control). On recirculation, the Na+,K+-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0
1

Year Published

1983
1983
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(20 citation statements)
references
References 34 publications
(26 reference statements)
0
19
0
1
Order By: Relevance
“…In that study, Na +,K+ ATPase activity was reduced slightly less after 60 min than after 30 min of MCA occlusion in compar ison to the nonischemic hemispheres, even though further decreases were observed at 2 and 4 h. Nei ther water content nor cation concentrations changed at 30 min, but these values later decreased progressively from 1 to 4 h after the onset of MCA occlusion. The partial temporary recovery of ATPase activity may have been due to a transient improvement in collateral circulation or excitotoxic cell activity during ischemia (MacMillan, 1982;Strong et aI., 1983).…”
Section: Discussionmentioning
confidence: 99%
“…In that study, Na +,K+ ATPase activity was reduced slightly less after 60 min than after 30 min of MCA occlusion in compar ison to the nonischemic hemispheres, even though further decreases were observed at 2 and 4 h. Nei ther water content nor cation concentrations changed at 30 min, but these values later decreased progressively from 1 to 4 h after the onset of MCA occlusion. The partial temporary recovery of ATPase activity may have been due to a transient improvement in collateral circulation or excitotoxic cell activity during ischemia (MacMillan, 1982;Strong et aI., 1983).…”
Section: Discussionmentioning
confidence: 99%
“…Restoration of circulation and substrate supply are necessary for repletion of cellular ATP stores and return to normal levels of pH and ion concentrations. MacMillan (27) reported that EEG recovered in parallel with the recovery of Na-K-ATPase activity over 72 h after global ischemia in rat forebrain. Thus, although metabolic recovery is necessary for electrophysiological recovery, the two are not necessarily contemporaneous and there are numerous experimental models in which the EEG recovers more slowly than cerebral energy metabolism, as reflected by brain oxygen consumption, high-energy phosphate content, and intracellular pH (28).…”
Section: Discussionmentioning
confidence: 99%
“…8 Using the four-vessel occlusion model, MacMillan 12 failed to observe a significant increase in cortical peroxide level for up to 72 hours of recirculation. These data disagree with our findings.…”
mentioning
confidence: 99%